2009
DOI: 10.1080/09537100802613449
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle modification decreases the mean platelet volume in prehypertensive patients

Abstract: Mean platelet volume (MPV) is an indicator of platelet activation. The present study was designed to investigate platelet function by measuring MPV, platelet count (PLC) and platelet mass (PLM) in prehypertensive (PHT) subjects. Additionally, we also evaluated the effects of lifestyle modification on platelet functions by measuring MPV, PLC and PLM. We selected 36 newly diagnosed PHT patients and 21 control subjects (BP < 120/80 mmHg) matched for age and sex. Lifestyle modifications (weight loss, reduced sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 34 publications
5
44
2
1
Order By: Relevance
“…However, in HT patients, both estimated parameters were significantly higher than in healthy controls, but only MPV levels significantly exceeded those observed in the PH group. Our results differ from those in the report by Yazici et al [50], who found increased MPV in pre-hypertensive subjects. However, the MPV in PH patients in their report was similar to our results, but the values of MPV were significantly lower in healthy controls.…”
Section: Discussioncontrasting
confidence: 57%
“…However, in HT patients, both estimated parameters were significantly higher than in healthy controls, but only MPV levels significantly exceeded those observed in the PH group. Our results differ from those in the report by Yazici et al [50], who found increased MPV in pre-hypertensive subjects. However, the MPV in PH patients in their report was similar to our results, but the values of MPV were significantly lower in healthy controls.…”
Section: Discussioncontrasting
confidence: 57%
“…The hypothesis of a causal association between platelet activation and prehypertension is supported by the evidence from intervention trials, suggesting a significant increase in MPV in prehypertensive subjects; these trials also showed a decrease in MPV after lifestyle modification for 20 weeks in a small sample of patients. 33 Further, prospective studies on the longitudinal association between MPV in relation to changes in blood pressure and prehypertension will help elucidate the true nature and magnitude of the association. Second, our study took place in a single center from a large urban teaching hospital, and the study population was a relatively homogeneous population in which a number of risk factors had been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…As the association of these variables was mainly directed towards a risk profile for cardiovascular disease, such an association might become stronger in pathological conditions, such as diabetes, obesity and hypertension. [35][36][37] Environmental variables, including dietary habits, did not show any relevant association with platelet indices.…”
Section: Other Variablesmentioning
confidence: 99%